Profitable entry into an unprofitable market - Ahmad Reza Saboori Memar (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
This paper shows how market entry into an unprofitable market can be profitable for a firm. A firm's expansion into a new market can have a beneficial feedback effect for that firm in its old market. By entering into a new market, the firm increases its produced quantity and has higher incentives to invest in process R&D. This is a credible signal to the competitors that the firm will be more aggressive in its R&D investments. This weakens the competitors since they scare off and invest less in process R&D. This feedback effect of expanding in foreign markets increases the profits of the expanding firm in its 'old market' and if this profit gain exceeds the losses through market entry, then the market entry is profitable for the firm. I also consider how the results change under Bertrand vs Cournot regime and how results change if price discrimination is possible or not. Beside that I show how higher R&D costs or lower demand in a market can lead to lower profits of one firm, but higher profits of the other firm.
Keywords: L13; D43; O30; 330; research and development; price discrimination; product differentiation; process innovation; interbrand competition; strategic commitment; separated markets